2022
DOI: 10.1186/s13023-022-02533-0
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic and dentofacial orthopedic treatments in patients with ectodermal dysplasia: a systematic review

Abstract: Objective The objective of this systematic review was to determine the orthodontic and dentofacial orthopedic treatments carried out in patients with ectodermal dysplasia to facilitate functional and aesthetic rehabilitation. Methods The systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analysis statement. We systematically searched PubMed, Web of Science, Scopus, Scielo, LILACS, EBSCOh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
(190 reference statements)
0
7
0
4
Order By: Relevance
“…The articles selected in the present study showed that the aligners are created by computer software, require only one impression, require few complementary exams, and allow excellent predictability of the treatment, when used within their indications [1,2]. They have a satisfactory aesthetic level, are comfortable, easy to clean, cause less trauma when compared to conventional fixed appliances, are less uncomfortable for patients since they can be removed and placed back without difficulty by the patient, and demonstrate excellent results.…”
Section: Major Findings -Aligner Plates In Orthodonticsmentioning
confidence: 95%
See 4 more Smart Citations
“…The articles selected in the present study showed that the aligners are created by computer software, require only one impression, require few complementary exams, and allow excellent predictability of the treatment, when used within their indications [1,2]. They have a satisfactory aesthetic level, are comfortable, easy to clean, cause less trauma when compared to conventional fixed appliances, are less uncomfortable for patients since they can be removed and placed back without difficulty by the patient, and demonstrate excellent results.…”
Section: Major Findings -Aligner Plates In Orthodonticsmentioning
confidence: 95%
“…They have a satisfactory aesthetic level, are comfortable, easy to clean, cause less trauma when compared to conventional fixed appliances, are less uncomfortable for patients since they can be removed and placed back without difficulty by the patient, and demonstrate excellent results. in light and moderate crowding [2].…”
Section: Major Findings -Aligner Plates In Orthodonticsmentioning
confidence: 99%
See 3 more Smart Citations